Peranan Nilai Kearifan Lokal “Balale” sebagai Modal Sosial Petani Dayak Banyadu dalam Penguatan Ekonomi Keluarga - Salfarini, Eligia Monixa; Sari, Maya; Atlantika, Yeremia Niaga; Dedy (Valid: Jurnal Ilmiah, 2025)
Balale culture plays an important role among Dayak Banyadu farmers. The values contained in balale culture become social capital that helps Dayak Banyadu farmers in social life. Balale culture is always lived by the community through various activities in the village, especially in terms of farming. This study aims to examine the role of balale culture as social capital for the Dayak Banyadu community in improving the family economy. Using qualitative research methods, data was obtained through observation and interviews with participants. The participants selected were local farmers who still apply balale culture in farming activities, which is the main livelihood of the Dayak Banyadu community. Data were analyzed using the triangulation method, where data were organized, reduced, and codified to draw conclusions regarding social capital through balale culture in supporting the economy of farming families. The results showed that balale culture contributes to the family economy of farmers in Dayak Banyadu through the values of love, brotherhood, respect, responsibility, solidarity and cooperation